Pervasive computing in sport - Fister, I.; Fister Jr., I.; Fister, D. (Computational intelligence in sports, 2018)
Pervasive computing has emerged with the advent of mobile technology. The aim is to be able to obtain information everywhere, at any time, for any objective. Consequently, the concept of disappearing hardware has been developed, where computers are hidden from the users perceptions. This is made possible through the use of sensors that are capable of converting physical events to equivalent electrical signals and transmitting them to a central computer. Indeed, the pervasive applications represent the main power of pervasive computing.